Studies on shrikhand rheology - Kulkarni, C.; Belsare, N.; Lele, Ashish K. (Journal of Food Engineering, 2006)
Shrikhand, a popular Indian dessert made from yogurt, is manufactured on an industrial scale using several chemical engineering unit operations such as mixing, filtration and heat transfer. Understanding the rheology of shrikhand is not only relevant for designing large scale mixers but can also provide quantitative means for linking the microstructure of shrikhand to its perception of texture, consistency and taste. We show here that shrikhand exhibits a combination of several rheological properties such as weak gel-like viscoelasticity, an apparent yield stress, thixotropy and long structural recovery time scales. For instance, the elastic modulus is always higher than the loss modulus over the measurable frequency range and that both moduli show only weak frequency dependence that is a characteristic of gel-like consistency. Forward and reverse rate sweep tests show a distinct hysteresis loop, which is a signature of thixotropic character. In an attempt to trace the origins of these rheological properties in shrikhand we characterized its microstructure and showed that there exist two different microstructures: one composed of crystallites of milk fats having a length scale of similar to 50-100 mu m, and the other composed of aggregates of colloidal cascin micelles of similar to 0.5-10 mu m size. Our studies show that while the temperature sensitivity of the viscoelastic parameters is dominated by the semicrystalline milk fat microstructure, the shear sensitivity is largely dictated by the protein network. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Microstructure; Rheology; shrikhand

Synthesis and characterization of novel hydrophobically end-capped poly(ethylene oxide)s [PEOs] - Badiger, Manohar V.; Kadam, Vijay S.; Lele, Ashish K.; Wadgaonkar, P. P.; Hourdet, Dominique (Macromolecular Symposia, 2006)
We report on the synthesis and characterization of a novel hydrophobically modified end-capped poly(ethylene oxide)s. The end-capping agent of this polymer was designed and synthesised from a renewable resource material namely, gallic acid (i.e. 3,4,5-trihydroxybenzoic acid), the byproduct of tannin industry. The hydroxyl groups at 3, 4 and 5 positions of gallic acid provide an opportunity for varying the hydrophobicity of the compound. The hydrophobic end-capping compound, 3,4,5tridodecyloxy bezoylazide was prepared from gallic acid and PEGS with different chain lengths (of number average molecular weights, 10000 and 35000 g/mol) were endcapped. using 3,4,5-tridodecyloxybenzoyl azide. The quantitative analysis of end-capping in the polymers was demonstrated by H-1-NMR spectroscopy and the rheological studies were carried out in the surfactant solutions.
Indo-French Symposium on Fibrillar Networks as Advanced Materials, Inst Charles Sadron, Strasbourg, FRANCE, SEP 21-23, 2005
Keywords: end-capped PEOs; hydrophobically modified polymers; water-soluble polymers

Simulation of viscoelastic flows of polymer solutions in abrupt contractions using an arbitrary lagrangian eulerian (ALE) based finite element method - Ganvir, Vivek; Lele, Ashish K.; Thaokar, Rochish; Gautham, Basavarsu P. (Journal of Non-Newtonian Fluid Mechanics, 2007)
We present a method for simulation of viscoelastic flows using an Arbitrary Lagrangian Eulerian (ALE) technique based finite element formulation. The ALE technique provides advantages of both Lagrangian and Eulerian frameworks by allowing the computational mesh to move in an arbitrary manner, independent of the material motion. In the present method, a fractional step ALE technique is employed in which the Lagrangian phase of material motion and convection arising out of mesh motion are decoupled. In the first step the relevant flow and constitutive equations are solved in Lagrangian framework. The simpler representation of polymer constitutive equations in a Lagrangian framework avoids the difficulties associated with convective terms thereby resulting in a robust numerical formulation. In the second step the mesh is moved in ALE mode and the associated convection of the stress is performed using a Godunov type scheme. This ALE technique is easy to implement and can accurately simulate the complex viscoelastic behaviour of transient polymer flow through complex geometries. In the present study, steady flows through abrupt contractions of planar and axisymmetric geometries are studied by performing transient flow simulations until steady state is achieved. The proposed method is validated with previously published numerical and experimental studies for polymer solutions obeying the Oldroyd B and Phan Thien Tanner (PTT) models. The simulated corner and lip vortex enhancement mechanism and flow behavior are in good agreement with experimentally obtained flow visualization photographs. The strength of the proposed method lies in its ability to simulate free surface flows such as swell. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: abrupt contraction; Arbitrary Lagrangian Eulerian; finite element; simulations

Self-diffusion coefficient of ring polymers in semidilute solution - Iyer, Balaj V. S.; Shanbhag, Sachin; Juvekar, Vinay A.; Lele, Ashish K. (Journal of Polymer Science Part B-Polymer Physics, 2008)
In a topologically constraining environment the size of a flexible nonconcatenated ring polymer (macrocycles) and its dynamics are known to differ from that of linear polymers. Hence, the diffusion coefficient of ring polymers can be expected to be different from linear chains. We present here scaling arguments for the concentration and molecular weight dependence of self-diffusion coefficient of ring polymers in semidilute solutions, and show that contrary to expectations these scaling relations are identical to what is known for linear polymers. At higher concentrations excluded volume interactions arising from possibilities of segmental overlap can become effective for large ring polymers. In this regime the diffusion coefficient of large ring polymers shows a relatively weaker dependence on concentration and molecular weight. (C) 2008 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys 46: 2370-2379, 2008
Keywords: Diffusion; Macrocycles; Monte Carlo simulation

Self-similar dynamics of a flexible ring polymer in a fixed obstacle environment: a coarse-grained molecular model - Iyer, Balaji V. S.; Lele, Ashish K.; Juvekar, Vinay A.; Mashelkar, Raghunath Anant (Industrial & Engineering Chemistry Research, 2009)
In this contribution we concern ourselves with an interesting problem, namely, the dynamics of ideal flexible ring polymers constrained in tin array of fixed obstacles. The fundamental issue in this problem is to understand how a topologically constrained polymer chain is able to relax its conformation in the absence of chain ends. The key physics was provided in tin elegant scaling theory by Rubinstein and co-workers (Obukhov, S. P; Rubinstein, M.; Duke, T. Dynamics of a Ring Polymer in a Gel. Phys. Rev. Lett. 1994, 73, 1263-1267). In this work we develop a coarse-grained mean-field model based oil the physical arguments of the scaling theory and derive constitutive relations for rings in fixed obstacle and melt environments. The model is composed of three distinct steps. In the first step the dynamics of an arbitrary section of a ring chain is worked out based oil fractal Blob-Spring (BS) dynamics, and the center of mass diffusion and the relaxation spectrum of this section are determined. In the second step the center of mass diffusion obtained using the BS dynamics is used to model the one-dimensional diffusion of the section in a topologically constrained environment. In the final step we invoke the idea of dynamic self-similarity and argue that the dynamics described in the first and the second step, for any arbitrary section of the chain, applies to all sections of the chain. The constitutive relation is obtained consequently as the superposition of dynamic response of all sections of the ring chain.

Some mechanistic insights into the gelation of regenerated silk fibroin sol - Nagarkar, Shailesh; Patil, Avinash; Lele, Ashish K.; Bhat, Suresh K.; Bellare, Jayesh R.; Mashelkar, Raghunath Anant (Industrial & Engineering Chemistry Research, 2009)
We provide some new insights into the kinetics and mechanism of sol-gel transition as it pertains to regenerated silk fibroin, which is the principle structural protein of silkworm silk fiber. Silk fibroin was dissolved in lithium bromide and dialyzed against deionized water to prepare a regenerated fibroin solution. This solution was found to be unstable at lower pH and transformed into a colloidal gel. The kinetics and mechanism of the sol-gel transition were investigated using rheology and light scattering. We show that gelation proceeds in two steps. In the first step, a weak gel is formed almost immediately upon lowering the pH, while in the second step further gelation proceeds rapidly after a long induction time to form a self-similar structure.

Synthesis of Sb-doped SnO2 nanowires and hyperbranched structures - Sathe, Bhaskar R.; Patil, Mrudula; Walke, Pravin S.; Vivek, J. P.; Lele, Ashish K.; Pillai, Vijayamohanan K.; Mulla, Imtiaz S. (Science of Advanced Materials, 2009)
Branched nanostructures of semiconducting materials are of great interest for their potential applications in optoelectronic, photonic devices and sensors. We herein describe a facile single-step chemical vapor deposition route for the synthesis of Sb-SnO2 hyperbranched nanostructures comprised of elongated nanowires with 30-40 nm diameter and 10-20 Am length. The morphology and structure has been characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), selective area electron diffraction (SAED), and powder X-ray diffraction (XRD). Also, a possible mechanism is proposed for the growth of nanowires into the hyperbranched form on the basis of the substrate effect, the role of Au nanoparticles, and the effect of Sb doping on specific morphology evolution. Interestingly, electrical conductivity measurements as a function of temperature suggest a semiconducting behavior, despite being governed by different electron-transport mechanisms with activation energies of 0.55 and 0.17 eV, which correspond to pure SnO2 and Sb-SnO2 nanowires, respectively. A precise control over the operating parameters not only envisages custom-designed, branched structures by a simple and economical route but also offers an alternative method to the expensive and tedious nanofabrication techniques for industrial applications.
Keywords: Au Nanoparticles; chemical vapor deposition; Sb-SnO2 Hyperbranched Nanostructures

Strain-rate frequency superposition in large-amplitude oscillatory shear - Kalelkar, Chirag; Lele, Ashish K.; Kamble, Samruddhi (Physical Review E, 2010)
In a recent work, Wyss et al. [Phys. Rev. Lett. 98, 238303 (2007)] have noted a property of ``soft solids'' under oscillatory shear, the so-called strain-rate frequency superposition. We extend this study to the case of soft solids under large-amplitude oscillatory shear (LAOS). We show results from LAOS studies in a mono-disperse hydrogel suspension, an aqueous gel, and a biopolymer suspension and show that constant strain-rate frequency sweep measurements with soft solids can be superimposed onto master curves for higher harmonic moduli with the same shift factors as for the linear viscoelastic moduli. We show that the behavior of higher harmonic moduli at low frequencies in constant strain- rate frequency sweep measurements is similar to that at large strain amplitude in strain- amplitude sweep tests. We show surface plots of the harmonic moduli and the energy dissipation rate per unit volume in LAOS for soft solids and show experimentally that the energy dissipated per unit volume depends on the first harmonic loss modulus alone, in both the linear and the nonlinear viscoelastic regime.

Structure and gelation mechanism of silk hydrogels - Nagarkar, Shailesh; Nicolai, Taco; Chassenieux, Christophe; Lele, Ashish K. (Physical Chemistry Chemical Physics, 2010)
Silk fibroin was regenerated from cocoons produced by the silkworm Bombyx Mori. Light scattering showed that an aqueous solution of the regenerated silk fibroin (RSF) was made of individual proteins with a weight average molar mass of about 4 x 10(5) g mol(-1) and a hydrodynamic radius of about 10 nm. Gel formation of RSF in acidic solutions was investigated as a function of the pH (2-4), concentration (0.5-10 g L(-1)) and temperature (5-70 degrees C). The structure of the gels was studied using light scattering and confocal laser scanning microscopy. The structure was found to be self-similar from length scales of less than 15 nm up to length scales of about 1 mm, and characterized by a correlation length of a few microns. Gel formation was tracked using turbidity, rheology, light scattering and circular dichroism. Gelation involves the formation of self-similar aggregates with a growth rate that increases exponentially. The protein aggregation is correlated to, and perhaps caused by, the formation of beta-sheets, the fraction of which also increases exponentially with time.

Star telechelic poly(L-lactide) ionomers - Kulkarni, Amruta; Lele, Ashish K.; Sivaram, Swaminathan; Rajamohanan, P. R.; Velankar, Sachin; Chatterji, Apratim (Macromolecules, 2015)
Poly(L-lactide) (PLA), a biodegradable and biorenewable polymer, has many excellent properties that are equivalent to those of petroleum-derived plastics such as polystyrene, aromatic polyesters, etc. However, a major disadvantage of PLA which limits its processability is its poor melt elasticity. In this work we explore the possibility of improving the viscoelastic properties of PLA melt by incorporating ionic groups on the polymer. Specifically, we demonstrate the synthesis of star telechelic PLA anionomers by a three-step procedure involving synthesis of Star PIA, converting the hydroxyl end groups into carboxylic acid end groups, and finally converting these into ionic groups. Rheology data showed a dramatic increase in the elasticity of the star telechelic ionomer melts relative to the Star PLA melts. The viscoelasticity of star telechelic ionomers melts could be modulated by varying the number of ionic groups per molecule.